Novel fabrication of functionalized graphene oxide via magnetite and 1-butyl-3-methylimidazolium tetrafluoroborate - Lim, J.; Mujawar, Mubarak; Khalid, M.; Abdullah, E.; Arshid, N. (2018)
© 2018 Elsevier B.V. The fabrication of functionalized graphene oxide via magnetite (Fe3O4) and ionic liquid into ferrofluid is investigated in this study. Several characterizations of the samples were made via Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM), and flame atomic absorption spectroscopy (FAAS).